Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Linking long-term soil phosphorus management to microbial communities involved in nitrogen reactions - R. M. O’Neill; A. M. Duff; F. P. Brennan; A. W. Gebremichael; N. T. Girkin; G. J. Lanigan; D. J. Krol; D. P. Wall; F. Renou-Wilson; C. Müller; K. G. Richards; C. Deveautour (Biology and Fertility of Soils, 2022)
The influence of soil phosphorous (P) content on the N-cycling communities and subsequent effects on N 2 O emissions remains unclear. Two laboratory incubation experiments were conducted on soils collected from a long-term (est. 1995) P-addition field trial sampled in summer 2018 and winter 2019. Incubations were treated with a typical field amendment rate of N as well as a C-amendment to stimulate microbial activity. Throughout both incubations, soil subsamples were collected prior to fertiliser amendment and then throughout the incubations, to quantify the abundance of bacteria (16S rRNA ), fungi (ITS) and Thaumarcheota (16S rRNA ) as well as functional guilds of genes involved in nitrification (bacterial and archaeal amoA, and comammox) and denitrification ( nirS , nirK , nosZ clade I and II) using quantitative PCR (qPCR). We also evaluated the correlations between each gene abundance and the associated N 2 O emissions depending on P-treatments. Our results show that long-term P-application influenced N-cycling genes abundance differently. Except for comammox, overall nitrifiers’ genes were most abundant in low P while the opposite trend was found for denitrifiers’ genes. C and N-amendments strongly influenced the abundance of most genes with changes observed as soon as 24 h after application. ITS was the only gene correlated to N 2 O emissions in the low P-soils while microbes were mostly correlated to emissions in high P, suggesting possible changes in the organisms involved in N 2 O production depending on soil P-content. This study highlights the importance of long-term P addition on shaping the microbial community function which in turn stimulates a direct impact on the subsequent N emissions.

Multiple primary malignancies associated with a germline SMARCB1 pathogenic variant - Judith A. Eelloo; Miriam J. Smith; Naomi L. Bowers; John Ealing; Paul Hulse; James P. Wylie; Patrick Shenjere; Noel W. Clarke; Calvin Soh; Richard W. Whitehouse; Mark Jones; Christopher Duff; et al. (Familial Cancer, 2019)

RBANS Validity Indices: a Systematic Review and Meta-Analysis - Robert D. Shura; Timothy W. Brearly; Jared A. Rowland; Sarah L. Martindale; Holly M. Miskey; Kevin Duff (Neuropsychology Review, 2018)

IL1B gene promoter haplotype pairs predict clinical levels of interleukin-1β and C-reactive protein - John Rogus; James D. Beck; Steven Offenbacher; Kenneth Huttner; Licia Iacoviello; Maria Carmela Latella; Monica de Gaetano; Hwa-Ying Wang; Kenneth S. Kornman; Gordon W. Duff (Human Genetics, 2008)